Features of Russian Agribusiness Grape-winery Subcomplex Modernization - Spakhgiraev, I U; Usenko, L N; Usenko, A M; Popova, L V; Kpamzatov, V A (KnE Life Sciences, 2019)
The article devotes to the analysis of the Russian agribusiness grape-winery subcomplex current state and to its development features description. The problems of viticulture and winery, that impede the subcomplex development and modernization, are highlighted. These problems are the inability of viticulture farms to satisfy the wineries need for raw materials fully, the high cost of growing grapes, cheap imported wine materials, the lack of competitiveness towards foreign producers, and necessary financial support absence. To develop the wine and wine industry in our country, it is necessary to implement a set of measures at the federal and regional levels. At the federal level, it is necessary to create an appropriate legal framework for high-quality winemaking, which would equally protect the interests of grapes and wine producers, wine trading and consumers. At the regional level, it is relevant to improve the material and technical base state of the viticulture of Russia, because nowadays the industry development does not meet the existing agro technical requirements and lags significantly behind the development of Western countries. Since 2001, the state policy of supporting agricultural production conducted in the last decade and the agroindustrial policy in Russia in general has tended to create a developed wine-growing sub-complex. Over the past few years, when modernizing this subcomplex, vineyards have been renovated, new highly productive varieties have been laid. These measures positively affect the grape production and yield and generally give hope for the grape industry development. Emphasis is placed on key areas, features and prospects for the modernization of the wine and wine subcomplex of Russian agroindustrial complex. This is the implementation of a set of measures at the federal and regional levels. The article describes vectors and stages of the implementation of state policy and financial support in the field of this subcomplex modernization, proposed by the Concept of the Development of Viticulture and Winemaking in the Russian Federation for the period 2016–2020 and the planning period until 2025.